Purchase Decision Analysis Through Price Policy And Brand Image - Edi Rahmat Taufik (Husnayain Business Review, 2021)
This study aims to analyze the price policy and brand image in relation to purchasing decisions. This type of research is quantitative research using a survey method of 95 respondents. Data collection uses a questionnaire as a data collection tool. Data analysis used validity test, reliability test, classical assumption test, multiple linear regression and determination analysis. AnaStatistical analysis shows that in partial testing the price variable has no effect on purchasing decisions, while brand image has a positive and significant effect on purchasing decisions. Furthermore, in simultaneous testing that price and brand image have a positive and significant effect on purchasing decisions. To find out the contribution of research variables (price and brand image) to purchasing decisions, it is carried out using analysis of the coefficient of determination, and the result is 0.43 or 43% and the rest of the purchasing decisions are influenced by other variables of 0.57 or 57%, namely other variables. for example advertising, product quality and others, which are not included in this research model. key word: Price, Brand Image, Purchase Decision.